Study of the Impact of Chronic Sleep Disorders on the Immune System and its Diagnostic Criteria - Rakhmatova Madina Fakhritdin qizi; Yakubova Marhamat Mirakramovna (Journal of Science in Medicine and Life, 2025)
According to WHO, every 3rd patient who consults a therapist complains of long-term (more than 1 month) problems falling asleep, daytime sleepiness, and frequent awakenings at night. This symptomatology indicates the development of a pathology such as chronic insomnia in a person. Epidemiological studies have shown that people with sleep problems are at increased risk of developing immune and chronic inflammatory diseases. Since sleep disorders and poor sleep quality are common disorders in the general population, it seems important to recognize them as serious health problems. The exact relationship between immunity and sleep remains unclear; however, it can be assumed that it is formed due to the stress of others and changes in circadian rhythms (often due to, for example, shift work). Studies show that drugs used to treat chronic inflammatory diseases, such as steroids or monoclonal antibodies, have a more complex effect on sleep than those that occur when symptoms of the disease subside. Interestingly, the relationship between sleep and immunity appears to be bidirectional; that is, sleep may affect the course of immune diseases such as inflammatory bowel disease. Thus, proper diagnosis and treatment of sleep disorders are crucial for the patient's immune system and, indeed, health. This review reviews the epidemiology of sleep disorders and immune disorders, the associations between them, and their current treatment and new perspectives on therapy.